Religious mobility and social contexts within neopentecostal mega-churches in Lima, Peru. - Ihrke-Buchroth, Uta (2013)
Peru of the 21st century is characterized by an atmosphere of progress and upward social mobility among its different social classes. An economy growing at a rate of approximately 8% annually is reflected in all of Peru but especially in the capital city of Lima. Greater Lima, with more than nine million inhabitants, represents approximately 30% of the Peruvian population and a multicultural mix of people from the country’s different provinces. Due to the existing centralism, Lima is the place where the Peruvian upper class live and the upwardly mobile migrate.